CFD model of the coal carbonization process. (15th June 2015) - Słupik, Łukasz; Fic, Adam; Buliński, Zbigniew; Nowak, Andrzej J.; Kosyrczyk, Ludwik; Łabojko, Grzegorz
Highlights: The model is developed to investigate thermal and flow processes within a coke oven. The model allows to simulate moisture evaporation. The numerical model was validated. Abstract: A 2D transient model of coupled heat and mass transfer phenomena occurring in a single coke chamber is developed. The interior of the chamber is partially filled by the coal charge, which is assumed to be a porous media. The standard equations of continuity, species transport, momentum and energy describing the flow of the single-phase fluid are applied. The model considers a range of aspects associated with the carbonization process, such as the evaporation and condensation of the water, the evolution of the volatile components, the change in the density and the flow resistance during the coking process. Conductive, convective and radiative types of heat transfer are included in the model. The model also provides for the creation of the lateral gap near the walls. Water evaporation and condensation are modeled with the modified Hertz–Knudsen equation linked to the sorption isotherm. The model of the specific process is implemented in the commercial CFD software ANSYS Fluent. Results of the CFD simulation are compared with thermocouple measurements performed at the Centre de Pyrolyse de Marienau test unit. Commonly known information regarding raw gas evolution and energy consumption are also used for validation purposes. The model agrees well with both experimental data and data from the literature.